CHARACTERIZATION AND DEVELOPMENT OF ROTAVIRUS RV4 LIKE PARTICLE VACCINE CANDIDATE COMPONENTS IN VERO CELLS - Rahmah, Latri
Rotavirus has been recognized as a major cause of infantile diarrhea in young children. Classified as a non-enveloped Reoviridae virus, the genome of Rotavirus consist of 11 dsRNA that encodes 6 structural and 6 nonstructural proteins. The structure of Rotavirus is composed of three layers (outer, inner and core) capsid protein. The core layer is constructed with 120 molecule proteins of VP2 as the major protein and VP1-VP3 minor proteins. The Rotavirus inner layer is composed of 780 VP6 capsid proteins. The Rotavirus outer layer is composed of VP7 and VP4 capsid proteins. Core, inner, and outer layer genes of Human Rotavirus RV4 had been isolated and cloned into mammalian expression system.VP2 gene (VP2LRV4) with a size of 2673 bp, was cloned into pcDNA 3.1/CT-GFP-TOPO while VP6 (VP6LRV4) and VP7(VP7LRV4) gene with size 1194 and 981 bp had been cloned into pEF6/V5-His-TOPO. The Genes of VP2LRV4, VP6LRV4, and VP7LRV4 had been fully sequenced and characterized. VP2LRV4 sequence showed 99% similarity with Human Rotavirus G1P(8) (gb|KC579893.1), VP6LRV4 sequence showed 98% similarity with Human Rotavirus G1P(8) (gb|JN 258848.1), and VP7LRV4 sequence showed 99% similarity with Human Rotavirus G1P(8) (dbj|AB971568.1). Protein structure (prediction) of VP2LRV4 showed a domain that was predicted to be a VP2 dimer domain. VP6LRV4 showed domain B (residues 1-150), domain H (residues 151-331) and His-153 that were predicted to be domains and residues involved in the formation of VP6 trimer. VP6LRV4 also contain residues Leu65, 70, and 71 that were predicted to interact with VP2 to form Double Layer Particle (DLP). Other important residues in VP6LRV4 were Pro279 and Thr281 that were predicted to interact with residues Pro313 on VP7LRV4. VP2LRV4, VP6LRV4, and VP7LRV4 sequences contained epitopes in their sequences. VP2LRV4 sequence “SLISGMWLL” was predicted to be recognized by CD8 + T cells. VP6LRV4 amino acid sequence “FQLMRPPNM” was predicted to be recognized by CD4+ T cells and sequences “TLLANVTAV” was predicted to be recognized by CD8+ T cells. VP7LRV4 amino acid sequence “PTTNPQTERMMRVNWKKWWQV” was predicted to be recognized by B cells. iv Expression vectors pcDNA/VP2, pEF/VP6, and pEF/VP7 was transfected and cotransfected into Vero cells. Gene transcription and protein expression were analyzed using RT-PCR and immunofluorescence assay (IF). VP2 cDNA expression showed a band of the appropriate size on day 3 post-transfection, while VP6 and VP7 showed bands of the appropriate sizes on day 1 posttransfection. Co-transfection results showed that VP2 cDNA was expressed on day 4 post co- transfection while VP6 and VP7 cDNA was expressed on day 3 to day 5 post co-transfection . VP6 and VP7 protein expression marked with fluorescent luminescence in Vero cell transfectant on day 1 to day 5 post-transfection and day 3 to 5 post cotransfection. Electron Microscopy analysis in Vero Cells co-transfectant revealed the form of particle with size ±80 nm though it could not be assured yet the formation of monolayer VLP, DLP or TLP Rotavirus.